Perlindungan Hukum Terhadap Penumpang Pesawat Atas Keterlambatan Penerbangan (Flight Delayed) - Yuliana, Tora (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
In recent years there have been frequent flight delays which have caused passengers as consumers to feel disadvantaged. When passengers complain to the airline, sometimes the airline ignores and throws the responsibility. The problems of this research: 1) how is the airline's responsibility towards airplane passengers who are harmed due to flight delays in terms of the aviation law and the consumer protection law. 2) how is the legal protection for passengers who are harmed due to flight delays in terms of the aviation law and the consumer protection law. 3) what is the court's decision on the lawsuit Number 309/Pdt.G/2007/PN.Jkt.Pst between David M.L.Tobing, S.H., M.Kn and PT. Lion Mentari Air Lines. This type of research is normative research, through a statutory and conceptual approach. Data processing is carried out through the stages of data selection, data classification, compilation of data which is then analyzed. The results of the study show that the responsibility of airlines according to Law No.1 of 2009 concerning flights adheres to the concept of presumption of guilt, meaning that the carrier is automatically responsible for flight delays. The responsibility of the airline as a carrier to passengers is obliged to provide compensation or compensation. This is reinforced by the Regulation of the Minister of Transportation No. 77 of 2011 concerning the responsibility of air carriers and the Regulation of the Minister of Transportation No. 49 of 2012. Regarding this responsibility, it is also reinforced by consumers and airlines as business actors. This is one of the legal protections for passengers for the negligence of the carrier, but if the carrier does not perform its obligations then the passenger has the right to take legal action to claim rights. Like the case of David M.L.Tobing, S.H., M.Kn who filed a lawsuit to the district court, this was done so that the rights of passengers as consumers who were harmed were not toyed with and it was a lesson for every airline to better serve passengers. The decision of the Central Jakarta District Court No.309/Pdt.G/2007/PN.Jkt.Pst, especially on the standard clauses on passenger tickets, is very precise and relevant.